1988
DOI: 10.1128/mcb.8.6.2309
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus middle T antigen induces ribosomal protein S6 phosphorylation through pp60c-src-dependent and -independent pathways.

Abstract: Phosphorylation of ribosomal protein S6 is elevated in polyomavirus-infected cells. This elevation results only in part from activation of S6 kinase activity. These effects appear to reflect independent activities of wild-type middle T antigen. Hr-t mutant NG59, encoding a defective middle T protein, and mutant Py8O8A, encoding no middle T protein, were unable to induce S6 kinase activity or elevate S6 phosphorylation. Two other site-directed mutants encoding altered middle T proteins did elevate S6 phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
1

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
(52 reference statements)
1
10
1
Order By: Relevance
“…This study extends an earlier report on polyomavirus-induced elevation of ribosomal protein S6 phosphorylation (68) by demonstrating activation of pp70 S6K in a pathway mediated by mT and PI3K. Genetic and biochemical evidence supports the conclusion that PI3K binding to mT is required for activation of both the cytoplasmic (70-kDa) and nuclear (85-kDa) forms of S6 kinase.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This study extends an earlier report on polyomavirus-induced elevation of ribosomal protein S6 phosphorylation (68) by demonstrating activation of pp70 S6K in a pathway mediated by mT and PI3K. Genetic and biochemical evidence supports the conclusion that PI3K binding to mT is required for activation of both the cytoplasmic (70-kDa) and nuclear (85-kDa) forms of S6 kinase.…”
Section: Discussionsupporting
confidence: 75%
“…Previous work has shown that two mT-dependent mechanisms contribute to increased S6 phosphorylation. One involves activation of an S6 kinase(s) and is dependent on mT activation of pp60 c-src ; the other is independent of mT-pp60 c-src interaction and may reflect negative regulation of an S6 phosphatase (68). How mT exerts these effects, and specifically whether pp70 S6K is in-volved, is unknown.…”
mentioning
confidence: 99%
“…Another kinase associated with growth factor stimulation, p70 S6-kinase , is activated by constitutively active mutants of PKB/Akt, but is not a direct substrate (Burgering and Co er, 1995). p70 S6-kinase activation has also been observed as a consequence of polyomavirus infection (Talmage et al, 1988;Dahl et al, 1996). The involvement of PKB/Akt in growth regulation is further supported by data obtained with an oncogenic form of PKB/Akt expressed as a Gag-PKB/Akt fusion protein by the acute retrovirus AKT8 (Bellacosa et al, 1991).…”
Section: Middle-t Activates Pkb/aktmentioning
confidence: 65%
“…The (39,40) and by expression of ras antisense RNA (41) or a dominant inhibitory mutant of ras (42), suggesting that both Src and Ras are required for MT-mediated transformation. Raf-1 and Rsk kinase activities are elevated in MT-transformed cells, but their involvement in MT-mediated alterations in gene expression and transformation has not been defined (16,17).…”
mentioning
confidence: 99%
“…These mutants recently were shown to be defective in binding the SH2-containing adaptor molecule, SHC, which is phosphorylated on tyrosine in MT-transformed cells and binds to GRB2, providing a plausible link between MT and Ras activation (15). Polyoma-transformed cells show increases in the activities of protein serine/threonine kinases, including Raf-1 (16) and ribosomal protein S6 kinase (17), and an increase in the activities of transcriptional regulators, PEA1/ AP-1 and PEA3/c-ets (18,19). Therefore, it seems likely that association of MT with proteins in the cell membrane induces signaling pathways that activate serine/threonine kinases and transduce signals to transcriptional regulators in the nucleus.…”
mentioning
confidence: 99%